Electromyographic study of the trapezius (pars media) and rhomboideus major muscles during respiration - De Freitas, V.; Vitti, M. (My University, 1980)
The authors studied the trapezius (pars media) and rhomboideus major muscles during deep inspiration and expiration. The electromyographic records demonstrated that these muscles showed no activity in either phase of breathing.
Keywords: breathing muscle; electromyography; human cell; muscle; normal human; respiratory system; rhomboideus major muscle; trapezius muscle; Adult; Electromyography; Human; Male; Respiration; Shoulder